Adaptive Occupational Health Strategies under Climate Change: Exploring Heat Stress Mitigation through Green Rooftop Design in Urban Workplaces - Sitti Rachmawati Yahya; Riris Johanna Siagian; Abdal Ahmed (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
Urban workers are increasingly vulnerable to heat stress due to rising global temperatures, especially in cities affected by the Urban Heat Island (UHI) effect. This heat stress poses significant risks to worker health and productivity, exacerbating health issues such as dehydration, heat exhaustion, and heat stroke, while also reducing work efficiency. The study aims to assess the effectiveness of green rooftop designs as a mitigation strategy for heat stress in urban workplace environments. Green rooftops are increasingly seen as a sustainable solution for urban heat management, offering benefits in temperature regulation, energy efficiency, and overall worker well-being. This study examines various heat stress mitigation strategies, including green roofs, industrial fans, and shading systems, focusing on their comparative effectiveness in reducing temperatures and improving worker comfort. The research involved environmental temperature measurements inside and outside urban workplaces, the use of wearable heat sensors to monitor workers’ heat stress levels, and building energy simulations to predict the impact of green rooftops on indoor climate control. Results indicate that green rooftops reduced workplace temperatures by an average of 3.8°C and decreased heat-stress-related complaints by 35%. In comparison to industrial fans and shading systems, green rooftops provided superior long-term relief, reducing heat stress and improving both worker productivity and environmental quality. The findings support the integration of green rooftops into urban workplace designs as a viable climate adaptation strategy. Future research should explore optimizing green rooftop designs for different climates and assessing their long-term benefits for worker health and urban resilience.